PENGARUH KEPEMIMPINAN PARTISIPATIF, IMBALAN FINANSIAL DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PT. NADIA KENCANA DI DENPASAR - Adnyana, I Gede Made Putra; Riana, I Gede (E-Jurnal Manajemen, 2015)
This study aimed to analyze the effect of participative leadership, financial rewards, and physical work environment to employees satisfaction PT. Nadia Kencana Denpasar. This research was conducted at PT. Nadia Kencana Denpasar by taking 54 samples of employees. The analysis technique used in this research is multiple linear regression. The number of samples obtained by using random sampling method is as much as 54 respondents. Based on the analysis found that participative leadership, financial rewards and physical work environment simultaneously significant effect on employee job satisfaction with the value of F (67.521)> F table (2.76). participative leadership, financial rewards and physical work environment partially positive effect on employee job satisfaction. This can be evidenced from the t value of participative leadership (3,488)> t table (1.671). Financial rewards (2,164)> t table (1.671). Physical work environment (2,203)> t table (1.671).
Keywords: kepemimpinan partisipatif; Imbalan finansial; lingkungan kerja fisik; Kepuasan kerja.